miR-22 has a potent anti-tumour role with therapeutic potential in acute myeloid leukaemia - Jiang, Xi; Hu, Chao; Arnovitz, Stephen; Bugno, Jason; Yu, Miao; Zuo, Zhixiang; Chen, Ping; Huang, Hao; Ulrich, Bryan; Gurbuxani, Sandeep; Weng, Hengyou; Strong, Jennifer; et al. (Nature communications, 2016)
MicroRNAs are subject to precise regulation and have key roles in tumorigenesis. In contrast to the oncogenic role of miR-22 reported in myelodysplastic syndrome (MDS) and breast cancer, here we show that miR-22 is an essential anti-tumour gatekeeper in de novo acute myeloid leukaemia (AML) where it is significantly downregulated. Forced expression of miR-22 significantly suppresses leukaemic cell viability and growth in vitro , and substantially inhibits leukaemia development and maintenance in vivo . Mechanistically, miR-22 targets multiple oncogenes, including CRTC1 , FLT3 and MYCBP , and thus represses the CREB and MYC pathways. The downregulation of miR-22 in AML is caused by TET1/GFI1/EZH2/SIN3A-mediated epigenetic repression and/or DNA copy-number loss. Furthermore, nanoparticles carrying miR-22 oligos significantly inhibit leukaemia progression in vivo . Together, our study uncovers a TET1/GFI1/EZH2/SIN3A/miR-22/CREB-MYC signalling circuit and thereby provides insights into epigenetic/genetic mechanisms underlying the pathogenesis of AML, and also highlights the clinical potential of miR-22-based AML therapy. Mir-22 has been shown to be an oncogenic microRNA in breast cancer and myelodysplastic syndrome. Here, the authors show that mir-22 functions as a tumour suppressor in de novo acute myeloid leukaemia by inhibiting the expression of several oncogenes and that restoring mir-22 expression suppresses AML progression.